Sharia-Based Customs in Unregistered Marriage Rules (Case Study in Rambatan Village, West Sumatra) - Khalilurrahman, Muhammad; Eficandra, Eficandra; Alfiander, Dodon (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
This study focuses on the factors causing the birth of customary rules, then forms of customary sanctions, and the implementation of customary rules, as well as analyzes the dynamics of implementing customary rules against unregistered marriages in the view of Islamic law.  The type of research conducted was field research.  Primary data sources were Ninik Mamak, Wali Jorong, Religious Counselors, perpetrators of unregistered marriages, and their relatives.  Secondary data sources were books and journals about marriage, customs, Islamic law and Positive law. The data were collected through semi-structured interviews and documentation techniques.  Data analysis and interpretation techniques were data reduction, data presentation and conclusions.  The technique of guaranteeing the validity of the data was by triangulation of sources.  The results of the study indicate that the cause of the birth of customary rules was because they were not in accordance with Islamic teachings, positive law, and were considered a disgrace to the people.  Forms of sanctions for the perpetrators of this unregistered marriage were expelled from the Nagari, if they were not pleased then paid a fine for slaughtering a goat, and if they did not want to do it, then they were set aside as long as the custom.  Those who paid the fine had to do so in public and apologized to Ninik Mamak.  Of the 11 pairs who performed unregistered marriages, 7 pairs were expelled from Nagari, 2 pairs paid a fine for slaughtering a goat, and 2 pairs were set aside from the custom.  This rule is in line with sadd al-zari'ah principles in Islamic law.